Effect of Processing on the Structure, Techno-Functional Properties and Nutritional Quality of Animal- and Plant-Based Food Proteins (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The processing of animal- and plant-based food proteins significantly impacts their structure, techno-functional properties, and nutritional quality. Techniques such as heating, extrusion, fermentation, and enzymatic hydrolysis alter protein conformation, leading to changes in solubility, emulsification, foaming, and gelation properties. For instance, heat treatment can denature proteins, improving digestibility but potentially reducing certain functional properties. Extrusion enhances texturization, making plant proteins more meat-like, while fermentation can improve bioavailability and reduce anti-nutritional factors in plant proteins. However, excessive processing may lead to the loss of essential amino acids or the formation of harmful compounds, such as advanced glycation end products (AGEs). Animal proteins generally exhibit higher stability during processing, whereas plant proteins may require additional modifications to achieve the desired functionalities. Balancing processing conditions is crucial to optimize both the techno-functional and nutritional attributes of proteins, ensuring they meet consumer demands for health, sustainability, and sensory appeal.